The Narrative Past Inflection in Sesotho Child and Child-Directed Speech - Riedel, Kristina; Sarvasy, Hannah; Demuth, Katherine (Frontiers in Communication, 2019)
This study investigates a low-frequency verbal inflection called the ‘narrative past’ in child and child-directed speech in the Bantu language Sesotho. Since the function of the Sesotho narrative past is not well-described, this study aimed to illuminate both function and acquisition trends in the Demuth Sesotho Corpus (Demuth, 1992). This construction has been assumed to be under-specified for tense, comparable in function to the better-known Swahili -ka- inflection. The Swahili form, in turn, has been said to function in ‘clause chains’ that are functionally and structurally similar to such chains in Papuan and other languages. We expected that if the Sesotho narrative past is indeed functionally similar to Swahili -ka-, its distribution in child-directed speech and acquisition by children may pattern similarly to tense-less verb forms in non-Bantu clause chaining languages such as the Papuan language Nungon, where such verb forms can comprise over 20% of all verb tokens in child-directed and child speech at age 3;3. This study thus examined the conversational interactions of four children acquiring Sesotho in a village setting, aged 2;1 to 4;7. All 492 tokens of the narrative past form were coded for syntactic and discourse categories. Results show that the Sesotho narrative past generally occurs in much ‘looser’ discourse chains than in the clause chains of languages like Nungon; for Sesotho, other turns or elements can intervene between narrative past-framed mentions of previously-introduced topics. Further, the Sesotho narrative past has very low frequency in both child and child-directed speech, representing less than 3% of all verb tokens for both registers. There is possible evidence that one of the target children uses the Sesotho narrative past in increasing proportions as his linguistic sophistication increases, though there is no proportional increase in child-directed speech. Thus, in function and distribution, in both child-directed and child speech, the Sesotho narrative past form differs greatly from tense-less forms in more canonical clause chaining languages.